2005
DOI: 10.1128/jvi.79.5.2678-2688.2005
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Modified Vaccinia Virus Ankara Expressing the Spike Glycoprotein of Severe Acute Respiratory Syndrome Coronavirus Induces Protective Neutralizing Antibodies Primarily Targeting the Receptor Binding Region

Abstract: Immunization with a killed or inactivated viral vaccine provides significant protection in animals against challenge with certain corresponding pathogenic coronaviruses (CoVs). However, the promise of this approach in humans is hampered by serious concerns over the risk of leaking live severe acute respiratory syndrome (SARS) viruses. In this study, we generated a SARS vaccine candidate by using the live-attenuated modified vaccinia virus Ankara (MVA) as a vector. The full-length SARS-CoV envelope Spike (S) gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
207
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 184 publications
(216 citation statements)
references
References 57 publications
8
207
1
Order By: Relevance
“…This observation may be explained by MERS-CoV-specific differences in receptor usage and entry mechanisms, as discussed previously (18). Previous work with SARS-CoV showed that S-specific neutralizing antibodies correlated with the protective capacity of vaccination in various animal models (18,26,27; for a review, see reference 28).…”
mentioning
confidence: 79%
“…This observation may be explained by MERS-CoV-specific differences in receptor usage and entry mechanisms, as discussed previously (18). Previous work with SARS-CoV showed that S-specific neutralizing antibodies correlated with the protective capacity of vaccination in various animal models (18,26,27; for a review, see reference 28).…”
mentioning
confidence: 79%
“…We have demonstrated that the antisera from SARS patients and from animals immunized with inactivated SARS-CoV reacted strongly with RBD (9,35). Absorption of antibodies by RBD from these antisera results in the removal of most of the neutralizing antibodies, and RBD-specific antibodies isolated from these antisera have potent neutralizing activity (35,36). We have also shown that rabbits and mice immunized with RBD produced high titers of neutralizing antibodies against SARS-CoV with 50% neutralizing titers at a >1:10,000 serum dilution (37).…”
Section: Vaccines Based On Fragmentsmentioning
confidence: 93%
“…data). The antibodies purified from the antisera against SARS-CoV significantly inhibited RBD binding to ACE2 (9,(36)(37)(38). Using spleen cells from mice immunized with RBD, we have generated a panel of 25 monoclonal antibodies (MAbs) that recognize different conformational epitopes on RBD and possess potent neutralizing activity (38).…”
Section: Vaccines Based On Fragmentsmentioning
confidence: 99%
“…A recombinant vesicular stomatitis virus (VSV) expressing the SARS-CoV S protein was protective in mice (14) but has not been tested in primates, and the safety of VSV in humans remains to be established. Recombinant modified vaccinia Ankara (MVA) virus expressing SARS-CoV S protein was immunogenic and protective in rodent and primate models (15)(16)(17); however, one group found that the MVA/SARSCoV S-immunized ferrets developed hepatitis upon challenge with SARS-CoV (17). Vaccine constructs based on replication defective human adenovirus type 5 expressing a partial or full-length SARSCoV S protein have been evaluated for immunogenicity in rats and monkeys (18,19), but immunization depends on a high vaccine dose, and safety and protective efficacy remain to be demonstrated.…”
mentioning
confidence: 99%
“…An additional limitation of previous studies of vectored and inactivated SARS-CoV vaccines in non-human primates, the model that is most similar to humans, is that protective efficacy was measured by quantitation of challenge SARS-CoV shed in respiratory secretions (6,7,16,20). It is now known that the virus replication in nasal and lung tissues occurs at a much higher level than previously appreciated and is poorly represented by shed virus (24).…”
mentioning
confidence: 99%